5x+4(7)=3

Simple and best practice solution for 5x+4(7)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+4(7)=3 equation:


Simplifying
5x + 4(7) = 3

Multiply 4 * 7
5x + 28 = 3

Reorder the terms:
28 + 5x = 3

Solving
28 + 5x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -28 + 5x = 3 + -28

Combine like terms: 28 + -28 = 0
0 + 5x = 3 + -28
5x = 3 + -28

Combine like terms: 3 + -28 = -25
5x = -25

Divide each side by '5'.
x = -5

Simplifying
x = -5

See similar equations:

| -1=2+-0.5y | | 8X+7X+15=180 | | 15=5(4-x)+10 | | x^2+y^2+10x-4y+29=4 | | 5(23-4y)+4y=3 | | 8w-w+8w= | | m^2+4m-12=-7 | | (24p^14xq^18)^1/2 | | -1=2+-0.5 | | 12/2118/x | | y=4*tan(x) | | -11x+4=24 | | 600=.75x-(650+.5x) | | (66+30)*x=360+30*x | | 6×1/4 | | 5/1=1/3 | | 27x=0 | | (66+30x)=360+30x | | 9/32/5 | | 3x+20+10x-21=90 | | -4x+9y=81 | | (-5-1)-2f=-2(3-5) | | (5x-7)(7x+9)=0 | | -100(x+4)+54=-13-13 | | 5(x-2)=-9(x+1)+17 | | 12/21=18/x | | 66+30x=360+30x | | (5x+5)(5x^2+3x+2)= | | 3(4z+3)= | | -3(7.5+-3y)-2y=5.5 | | 6/5 | | 23-13=2(x-8) |

Equations solver categories